Over-qualified or under-skilled: A review of existing literature - Quintini, Glenda (Paris, 2011)
"Mismatches between workers’ competences and what is required by their job are widespread in OECD countries. Studies that use qualifications as proxies for competences suggest that as many as one in four workers could be over-qualified and as many as one in three could be under-qualified for their job. However, there is significant variation across countries and socio-demographic groups. Our meta-analysis of country studies suggests that over 35% of workers are over-qualified in Sweden compared with just 10% in Finland, with most other OECD countries located between these two extremes. There is also extensive evidence that youth are more likely to be over-qualified than their older counterparts and the same is found to be true for immigrant workers compared with a country’s nationals. On the other hand, no definitive evidence has been found of the persistence of qualification mismatch, with some papers showing that over-qualification is just a temporary phenomenon that most workers overcome through career mobility and others finding infrequent transitions between over-qualification and good job matches. Across the board, over-qualified workers are found to earn less than their equally-qualified and well-matched counterparts but more than appropriately-qualified workers doing the same job. Under-qualified workers are found to earn more than their equally-qualified and well-matched counterparts but less than appropriately-qualified workers doing the same job. Over-qualified workers are also found to be less satisfied about their job and more likely to leave their work than well-matched workers with the same qualifications."